AKPIN fintech application as one of the drivers for non-state pension system development - E. V. Knyazev; M. L. Dorofeev (Вестник университета)
The article studies the subject of improving the non-state pension provision mechanism considering the fintech application implementation into the system. The purpose of the study is to develop an application conceptual model in the framework of pension planning and individual pension strategies formation considering constant monitoring of changes in the legislative, economic, and other spheres to create an additional way for citizens to independently form long-term savings for developing the third level of the pension system. Information synthesis and analysis, available literature review, comparison, the results obtained formalization and specification have been carried out. The paper presents problems and analysis of existing programs to motivate long-term savings and proposals in the field of pension savings formation for developing the third level of pension provision. AKPIN fintech-application will allow to develop individual strategies for pension savings formation and will be aimed at a long-term strategy implementation for developing the accumulative component of the pension system in Russia. The proposed application has the ability to analyze the user’s data and, based on it, offer recommendations to increase their savings. If the user decides to spend funds, it can also issue recommendations on request. Due to continuous monitoring of the news background, financial regulators’ actions, financial indicators and changes in legislation, the application can offer up-to-date recommendations and assist users in making effective individual decisions in the area of pension savings management for citizens of the Russian Federation.